Kit for assaying activation of terminal complement cascade - FRANK; MICHAEL M; HAMMER; CARL H; JOINER; KEITH A; SANDERS; MARTIN E (1989)
A kit for assaying the activation of terminal complement cascade is disclosed. The kit includes a plurality of containers which contain a first antibody having a specificity for poly C9 neoantigen. The containers further have a second antibody which is different from the first antibody and has a specificity for a constituent of terminal complement cascade. A third antibody is optionally present which recognizes the second antibody. The kit also includes a substrate splitting enzyme, a substrate for the enzyme which produces a color reaction when split, and a SCb-9 standard microtiter plate. Pipettes and instructions for performing the assay are also included.